The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/afe.12396
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of a model biocontrol agent (Serenade® MAX) in apple and pear by mason bees and bumble bees

Abstract: 1 Biocontrol agents (BCAs) are commonly sprayed on flowering pipfruit trees to prevent them from getting infected by various pathogens. By entomovectoring, BCAs can be directly delivered onto the flowers. However, we currently lack knowledge on the distribution dynamics of BCAs by pollinators. 2 Here, managed bees, both bumble bees (Bombus terrestris) and mason bees (Osmia bicornis and Osmia cornuta), were placed in the vicinity of flowering pipfruit trees (pear -'Conference', and apple-'Svatava' and 'Jonagold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Because of the alleged safety towards non-target insect species, especially managed pollinators, honey bees, bumblebees, and mason bees have also been used as direct vectors to deliver biological control agents (BCA) against crop pests (Al Mazra'awi et al, 2006;Menzler-Hokkanen and Hokkanen, 2017;Maebe et al, 2021). The use of pollinating insects to spread BCA has its origin in the early '90s and in the last 15 years "pollinator-and-vector technology" has been systematically developed to improve sustenaibility, yield and quality in organic crop production (Smagghe et al, 2020).…”
Section: Biopesticides: Pros and Consmentioning
confidence: 99%
“…Because of the alleged safety towards non-target insect species, especially managed pollinators, honey bees, bumblebees, and mason bees have also been used as direct vectors to deliver biological control agents (BCA) against crop pests (Al Mazra'awi et al, 2006;Menzler-Hokkanen and Hokkanen, 2017;Maebe et al, 2021). The use of pollinating insects to spread BCA has its origin in the early '90s and in the last 15 years "pollinator-and-vector technology" has been systematically developed to improve sustenaibility, yield and quality in organic crop production (Smagghe et al, 2020).…”
Section: Biopesticides: Pros and Consmentioning
confidence: 99%
“…Honey bee (or also bumble bee) hives can be fitted with special dispensers of biological control agents (bacteria, fungi, viruses) that are antagonistic to microbial pathogens and pest insects (Kevan et al, 2003). Maebe et al (2021) Shimanuki and Knox (2000) indicated the wax month (Galleria mellonella Linnaeus c , Achroia grisella Fabricius c , Ephestia kuehniella Zeller c ), small hive beetle (Aethina tumida Murray c ) and the beelouse (Braula coeca Nitzsch c ) as the honey bee pests. Abou-Shaara and Staroň (2019) also included Varroa destructor Anderson and Trueman c mites (Figure 1), Vespa Linnaeus c hornets and parasitic flies into the group of honey bee pests.…”
Section: Bee Vectoring Technologymentioning
confidence: 99%